Pharmacognostic and Conservational Overview of Swertia chirata Buch.- Ham. ex Wall., A Critically Endangered Himalayan Herb - Arjun Karmakar (Journal of Food Science and Nutrition Therapy - Peertechz Publications, 2016)
Background: Swertia chirata Buch.-Ham. ex Wall. is an endangered medicinal herb native to the temperate Himalayan region. The species holds immense ethnobotanical importance in India, Nepal, Bangladesh and Bhutan. The herb is known to host a plethora of bioactive phytoconstituents that imbue it with a wide variety of medicinal properties. Modern research has proven that extracts of S. chirata possess antioxidative, anticarcinogenic, antimalarial, anti-infl ammatory and hypoglycaemic activities. The present article aims at highlighting the medicinal importance of S. chirata along with a brief discussion about its bioactive phytoconstituents. The research work carried out for improving the germplasm conservation strategies for S. chirata have also been elucidated in this review. Methods: In-depth analyses of S. chirata have been performed to outline its phytochemical profile in order to gain a better understanding about its medicinal attributes. Various techniques have also been applied for in vitro germplasm conservation of S. chirata. Result: S. chirata contains numerous potent bioactive compounds that contribute to its medicinal value. The unsupervised exploitation of natural reserves of S. chirata by pharmaceutical companies has driven the species on the verge of extinction, thus making in vitro germplasm conservation of the same essential. Conclusion: The importance of S. chirata as a cure for numerous ailments and health disorders has been welldocumented in traditional and modern medicine. The application of various modern techniques has not only allowed scientists to identify numerous medicinally important compounds present in S. chirata, but also created a platform for maintaining adequate production of this versatile medicinal plant species.